Expert vs. novices dimensions of tagging behaviour in an educational setting - Špiranec, Sonja (Array, 2012)
The organization and representation of information and knowledge have always beenexclusively in the domain of professionals and experts. This has begun to change with the development of folksonomies as alternative, user-generated models of organizing information. The aim of this paper is to research the efficiency in tagging and folksonomy. The flexibility oftagging allows users to classify their collections of items in the ways that they find useful, but the personalized variety of terms can present challenges when searching and browsing. In order to determine the efficiency of tagging research evidence about the nature of tagging and tagging behaviour of specific user groups is needed. This paper contributes to research findings in this domain by presenting findings from a study exploring differences in expert and novices tagging. The research was conducted by giving freshman students, with no prior knowledge of tagging or indexing and therefore determined as novices, an article in the social bookmarking service Delicious. Based only on title, subtitle and abstract of the article every student was supposed to assign tags to that article and do the same after reading the whole article. The same procedure was repeated with postgraduate students from the Department of Information Sciences with sufficiently experience and knowledge in tagging and indexing. In this way differences or similarities between tagging by more advanced users and tagging by average/amateur users could be analyzed and compared. The research has surfaced differences in tag numbers and tag distributions. The findings indicate more precision and consistency in tagging of the expert group, indicating that education in tagging could raise the quality of folksonomies on the long term.